Strategi Peningkatan Kapasitas Manajerial dan Kepemimpinan: Mendukung Daya Saing Koperasi Bina Warga Sejahtera - Junaidi Efendi; Achmarul Fajar; Syaiful Syaiful (Lembaga Pengembangan Kinerja Dosen, 2024)
Cooperatives have a strategic role in supporting the local economy and improving community welfare. However, many cooperatives face challenges in managerial and leadership aspects that hinder their competitiveness. This article discusses the results of community service programs aimed at improving managerial capacity and leadership at the Prosperous Citizen Development Cooperative in Pamekasan. The approach used includes training, mentoring, and hands-on mentoring, with a focus on strengthening strategic planning, operational management, and innovative leadership skills. The target of the program is cooperative administrators and key members who have a strategic role in the organization. The results showed significant improvements in managerial skills, leadership mindsets, and member involvement in strategic decision-making. This program also has an impact on more professional cooperative management, increased competitiveness, and strengthening the cooperative's external network. However, the evaluation of the program identified several obstacles, such as participants' time constraints, low levels of digital literacy, and resistance to change. To overcome this obstacle, it is recommended that there be more focused continuous training, flexibility in implementation time, and collaboration with external parties such as the government and educational institutions. This article emphasizes the importance of strengthening the capacity of human resources to support the transformation of cooperatives into competitive economic entities. This approach not only provides internal benefits for cooperatives, but also contributes to the development of the local economy in a sustainable manner. Thus, this service model can be a reference for the development of cooperatives in other regions.